Profitability Ratio Analysis in Measuring Financial Performance of Islamic Banking Companies Listed on the IDX in 2023-2024 - Heryanto, M Fajar Rizky; Sari, Reonika Puspita; Fahlevi, Muhammad Ryan (Al-Mashrof: Islamic Banking and Finance, 2026)
Islamic banking in Indonesia continues to record positive asset growth, but this development is not always followed by stable profitability. Fluctuating economic conditions during the 2023-2024 period created challenges for Islamic banks in maintaining financial performance. This study aims to analyze the profitability performance of Islamic banking companies listed on the Indonesia Stock Exchange during 2023-2024 using GPM, NPM, ROA, and ROE ratios. This research used a descriptive quantitative method with secondary data obtained from the quarterly financial reports of Bank Syariah Indonesia, Bank Aladin Syariah, and BTPN Syariah. The results show that the profitability performance of Islamic banks fluctuated in each quarter. Bank Syariah Indonesia showed relatively good profitability performance with ROA in fairly good condition. Bank Aladin Syariah still recorded negative profits, causing ROA and ROE to remain below industry standards. Meanwhile, BTPN Syariah showed very good profitability performance, especially in the ROA ratio which was above industry standards. Overall, the growth of Islamic banking during 2023-2024 has not been fully supported by optimal profitability, so better operational efficiency and more effective asset and capital management are still needed.   Keywords:  Financial performance, financial statement analysis, Islamic banking